Learn Blackberry games development - Hamer, Carol; Davison, Andrew (New York : Distributed to the book trade worldwide by Springer-Verlag, 2010)
Provides information on creating and selling game applications for the Blackberry platform.
Gaming on BlackBerry -- BlackBerry application basics -- Game graphics and events with MIDP and RIM classes -- Adding a professional look and feel -- Security and selling your game -- Swingin' light saber -- Play a live opponent with SMS -- Using scalable vector graphics -- Creating role-playing games on the internet -- Remotely driven a (toy) sports car -- Fox and hounds -- Introducing 3D with JSR 239.
Includes index.
Keywords: Computer games -- Design; Computer games -- Programming; BlackBerry (Smartphone) -- Programming; Smartphones -- Programming; Computer games -- Design; Computer games -- Computer software; BlackBerry (Smartphone) -- Computer software; Cellular telephones -- Computer software